2011
DOI: 10.1182/blood-2011-02-339242
|View full text |Cite
|
Sign up to set email alerts
|

CD147 (Basigin/Emmprin) identifies FoxP3+CD45RO+CTLA4+-activated human regulatory T cells

Abstract: Human CD4 ؉ FoxP3 ؉ T cells are functionally and phenotypically heterogeneous providing plasticity to immune activation and regulation. To better understand the functional dynamics within this subset, we first used a combined strategy of subcellular fractionation and proteomics to describe differences at the protein level between highly purified human CD4 ؉ CD25 ؉ and CD4 ؉ CD25 ؊ T-cell populations. This identified a set of membrane proteins highly expressed on the cell surface of human regulatory T cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 51 publications
5
57
0
Order By: Relevance
“…The proteomics data set with its 5225 identified proteins by itself is a valuable repository for further Treg research. Although proteomics has been used to study Tregs, previous studies focused either on proteins identified by gel blotting (44) or selective differences in the expression of specific surface molecules (45) or protein kinases (46). One recent report used proteomics to study the FOXP3 complex with all of its interaction partners (47).…”
Section: Discussionmentioning
confidence: 99%
“…The proteomics data set with its 5225 identified proteins by itself is a valuable repository for further Treg research. Although proteomics has been used to study Tregs, previous studies focused either on proteins identified by gel blotting (44) or selective differences in the expression of specific surface molecules (45) or protein kinases (46). One recent report used proteomics to study the FOXP3 complex with all of its interaction partners (47).…”
Section: Discussionmentioning
confidence: 99%
“…Protein identifications were performed as described previously (Solstad et al, 2011;Solstad et al, 2010).…”
Section: Protein Identification By Lc-ms/msmentioning
confidence: 99%
“…Among the immune-response genes, TNFRSF8 and BSG attracted our interest because these genes were upregulated in the PP samples (Fig. 3A) and encode the activation markers CD30 and CD147, which have been associated with regulatory T cells (14,15), Th2-like response, and chronic T-cell stimulation (16,17), although these genes are also detected in other immune cell subsets (18). In addition, TNFRSF8 upregulation was associated with several downregulated genes in the "inflammatory response, cell death and cell-mediated immune response" IPA pathway network shown in Fig.…”
Section: Validation Studies Confirm Differential Gene Expression Pattmentioning
confidence: 99%